Interictal dysphoric disorder: a frequent psychiatric comorbidity among patients with epilepsy who were followed in two tertiary centers - Pedro Paulo Gomes do Nascimento; Carlos Henrique Oliva; Clelia Maria Ribeiro Franco; Lennon Mazetto; Alberto S. Yamashiro; Gerardo Maria de Araujo Filho; Elza Marcia Targas Yacubian (Arquivos de Neuro-Psiquiatria)
Psychiatric disorders are frequent among patients with epilepsy. Data in the literature have shown a heterogeneous clinical presentation of psychiatric disorders in patients with epilepsy. Interictal dysphoric disorder could be a specific psychiatric comorbidity associated with epilepsy, primarily in patients treated in tertiary centers. Objective The present study aimed to determine the prevalence of interictal dysphoric disorder among patients with epilepsy who were followed in two tertiary epilepsy services in Brazil. Method Sixty-five patients with epilepsy completed the Portuguese version of the Interictal Dysphoric Disorder Inventory. Results Thirty-three (50.7%) patients fulfilled the diagnostic criteria for interictal dysphoric disorder, although all participants answered positively to having at least one key symptom. Conclusion The high rate of patients with epilepsy who fulfilled the diagnosis of interictal dysphoric disorder confirms an association between epilepsy and psychiatric disorders. However, there is clearly a need to improve diagnostic tools to allow better differentiation between interictal dysphoric disorder and other psychiatric disorders.